Enhancing Project Management Education: Investigating the Effectiveness of Flipped Learning and Active Experiential Learning Approaches - Syed Abd Latif, Sharifah Rosfashida; T. Subramaniam, Thirumeni; Che Leh, Azmi; Hassanor, Mohd Tajuzzaman (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
This study proposes an in-depth investigation into the efficacy of combining flipped learning and active experiential learning methodologies within the context of project management education at Open University Malaysia. The primary aim is to overcome the shortcomings of the traditional lecture-based teaching approach, which often falls short in engaging students and equipping them with the practical skills required for effective project management in real-world scenarios. By transitioning towards a more student-centered model through the implementation of flipped classrooms, this research seeks to enhance student engagement, learning outcomes, and overall satisfaction with the course. Employing a mixed-methods approach, the study will involve quantitative and qualitative techniques to gather comprehensive data. This includes pre- and post-assessment of students' knowledge and understanding of project management principles, alongside surveys and reflective journals to capture students' perceptions of the learning experience. The participant base will consist of students enrolled in a project management course, allowing for direct observation of the pedagogical strategies' impacts. The anticipated outcomes of this research are twofold. Firstly, it aims to provide empirical evidence on the effectiveness of integrating flipped learning and active experiential learning in project management education. Secondly, it seeks to offer actionable insights for educators and educational institutions on how to design and implement more engaging and effective instructional strategies. Ultimately, this study aspires to contribute significantly to the literature on educational methodologies in project management, paving the way for enhanced educational practices and student preparedness for professional success.